Towards quantitative imaging using coded light - Andersson, David (Department of Physics, Lund University, 2025)
Spectral imaging allows for the simultaneous visualization of multiple different spectral bands of a scene, and is a powerful tool used in a range of contexts - from the color cameras in smart phones, to scientific imaging applications such as remote sensing and fluorescence microscopy. The progress within these fields of research is therefore intrinsically linked to the advances made for more efficient spectral capture. The most common solution to achieve spectral sensitivity in snapshot is to use a filter array which is fixed to the sensor at a manufacturing stage. This provides a compact, stable and permanent solution, suitable for uses where the spectral bands never need to be changed. However, in many scientific measurement scenarios, spectral flexibility - the ability to alter the spectral bands captured - is crucial in order for efficient capture to be possible. This thesis presents and discusses the camera-independent image multiplexing technique FRAME, Frequency Recognition Algorithm for Multiple Exposures, and demonstrates its ability to be used for quantitative measurements. FRAME, among other things, enables snapshot multispectral capture using a monochrome focal-plane array. Thanks to its camera independence, spectral bands can be tailored to fit the specific conditions of the measurement. Furthermore, the technique can be used in conjunction with specialized high capture-rate and intensified cameras, broadening the use of such technology. The work presented demonstrates these uses, as well as quantitative applications within temperature imaging and spray characterization that utilize intensity and spatial information respectively. The impact of image quality on neural network-based processing is also discussed, using data captured with and without coded light to suppress scattering in images, and the compatibility of multispectral FRAME and microscopic imaging is demonstrated. These advances within the field of coded light pave the way for the continued development of FRAME for quantitative imaging applications, assisting the progress of adjacent, applied research.
Keywords: Quantitative; Coded light; FRAME; Multispectral imaging